On the use of social networking services and the ability to socialize: evidence from Chinese children aged 10 to 15. Issue 49 (21st October 2022) - Li, Yunrong; Mora, Ricardo
ABSTRACT: We use longitudinal individual data from a nationally representative sample of Chinese children aged 10 to 15 to investigate whether restrictions on internet use for social interactions affect social skills among adolescents. First, we find that ( i ) for most children offline and online relations are complements so that online restrictions reduce their offline social relations; ( ii ) these negative effects are mostly invariant to the size of the online network; and ( iii ) for older children they are large and statistically significant even in the absence of network effects. Second, we find that offline social relations directly affect social skills while online social relations do not. These results are consistent with the view that the majority of adolescents use online technologies to intensify their offline social relations, which has a positive effect on their ability to socialize with others.